2022
DOI: 10.1038/s41550-022-01730-y
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray-quiet black hole born with a negligible kick in a massive binary within the Large Magellanic Cloud

Abstract: This is a repository copy of An X-ray-quiet black hole born with a negligible kick in a massive binary within the Large Magellanic Cloud.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 87 publications
7
53
0
Order By: Relevance
“…obeys the contidition that its CO core mass > 1.38 M ) we draw 2000 kicks and record the models that remain bound. In addition we also consider a rotational velocity criteria as the O star in VFTS 243 was inferred to have a spin velocity at least 180 km s −1 (Shenar et al 2022a). The original STARS models in BPASS do not take into account rotation in the evolution of the stellar interior (although it is considered in the orbital evolution).…”
Section: Models and Numerical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…obeys the contidition that its CO core mass > 1.38 M ) we draw 2000 kicks and record the models that remain bound. In addition we also consider a rotational velocity criteria as the O star in VFTS 243 was inferred to have a spin velocity at least 180 km s −1 (Shenar et al 2022a). The original STARS models in BPASS do not take into account rotation in the evolution of the stellar interior (although it is considered in the orbital evolution).…”
Section: Models and Numerical Methodsmentioning
confidence: 99%
“…The VFTS 243 system however seems to be the first undisputed discovery of a quiescent BH in a stellar binary. Reported by Shenar et al (2022a), it is found to be an O7+BH in the 30 Doradus region. The very precise measurements of the orbital components (P = 10.4031 ±0.0004 days, e = 0.017 ±0.012) and extensive observational data surrounding this object have the potential to provide improved observational constraints or clues on a number of bottle-★ E-mail: hfstevance@gmail.com necks in stellar evolution theory such as natal supernova (SN) kicks and the genealogies of the progenitor systems of BH+BH binaries.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations